Caracterização citotaxonômica de Synbranchus Bloch, 1795 (Teleostei, Synbranchidae) da Bacia do Alto Paraguai - Rodrigues, Mamynne Correa da Costa (2017)
Synbranchus Bloch, 1795 (Synbranchidae), popularly known as Muçum, is represented by three species, S. marmoratus Bloch, 1785, S. lampreia Favorito, Zanata & Assumpção, 2005 and S. madeirae Rosen and Rumney, 1972. These fish have great commercial importance in the region, as it is sold as baits for sport fishing. From the cytogenetic point of view, among the representatives already studied at Mato Grosso's Pantanal, three karyotypic patterns are verified in the genus: karyotypes with 2n = 42, 2n = 44 and 2n = 46 chromosomes, suggesting the existence of at least three distinct species. Therefore, the goal of the present work is to characterize cytogenetically by classical and molecular methods exemplary from different regions of the northern Mato Grosso's Pantanal, in order to confirm this information and verify how many and which are the species of Synbranchus that actually occur in the region and that are used by fishermen, in the trade of live baits. They collected 54 specimens in the regions of Pantanal in Poconé, Cáceres and Barão de Melgaço, which were submitted to classical and molecular cytogenetic procedures, and morphological and morphometric analysis. The occurrence of the three karyotypes was confirmed, with diploid numbers 2n = 42 chromosomes (4 m + 14 st + 24 a) represented the species Synbranchus aff. marmoratus, with a specimen with 2n = 43 chromosomes, indicating the occurrence of a supernumerary chromosome; 2n = 44 chromosomes (4 m + 2 sm + 2 st + 36 a), represented the species S. aff. lampreia, and 2n = 46 chromosomes (6 m + 2 sm + 10 st + 28 a), represented the species S. madeirae. The band C revealed markings heterochromatin constitutive in the centromeric and interstitial regions of almost all chromosomes, the supernumerary chromosome is completely heterochromatic. The nucleoli organizing regions were detected in different chromosomal portions, in the three cytotypes found. In the specimens with 2n = 42, these sites were located on the short arm of the acrocentric pair 14; in the specimens with 2n = 44 were located in the long arm of the acrocentric pair 5, and in the fish with 2n = 46 were located in the short arm of the metacentric pair 2. Fluorescent in situ hybridization (FISH) using the 5S rDNA probes revealed markings on a single pair of acrocentric chromosomes. The 18S rDNA probe revealed distinct patterns among the karyotypes analyzed coinciding with the AgRONs markers. Telomere probes revealed signals in the terminal regions of almost all chromosomes. PCA performed from the morphometry data did not differentiate the species; however, the pattern of staining and shape of the head, as well as cytogenetic data confirmed that there are at least three taxonomic units for the genus Synbranchus in the studied region, which need either to be described or be correctly identified.